ACOMPARATIVE HISTOLOGICAL STUDY OF THE RETINA IN TWO SPECIES OF IRAQI VERTEBRATES - Sh. A. Abid, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study aimed to recognize the histological structure of retina in the eye of two Iraqi vertebrates, the difference of the class, the environment and the nature of nutrition; Magpie Pica pica, and Brown Rat Rattus norvegicus. The results showed that, the retina of the Magpie is avascular, while retina in Brown Rat is vascular , in both species the retina consists of two main layers: Pigmented epithelium and Neural layer  which composed of nine layers are : Visual cells layer, Outer limiting membrane, External nuclear layer, External plexiform layer, Internal nuclear layer, Internal plexiform layer, Ganglion cell layer, Optic nerve fiber layer and Inner limiting membrane .The pigmented epithelium consists of cuboidal epithelial cells, extending cytoplasmic projection toward visual cells. Visual cell layer was composed of rods  and cones in magpie, while  in Brown Rat composed of  rods only. The outer plexiform layer is less thicker than the inner plexiform layer in both type. The number of rows outer nuclear layer less than a number of rows the inner nuclear layer in magpie, while The number of rows outer nuclear layer more than a number of rows the inner nuclear layer in Brown Rat. The retina has been characterized in magpie by the presence of fovea . It can be concluded that the differences in the density of visual cells in the species studied were due to increase visual acuity and light level sensitivity.